Perovskite Ceramics as New-Generation Materials for Orthopedic Applications - Dubey A.K.; Ravikumar K.; Basu B. (My University, 2025)
The piezoelectric properties of ferroelectric ceramics have been widely investigated in the materials science community, but relatively less is known about such properties of natural living system. Inspired by the knowledge that the piezoelectric properties influence the metabolic activities of natural bone, the design and development of bone-mimicking electrically active synthetic orthopedic implant materials has gained an excellent distinction in the biomaterials community. In this perspective, the present article briefly reviews the origin of fundamental electrical responses in natural bone along with their biological consequences. In this sequence, the potentiality of multifunctional electrically active perovskites (CaTiO3, BaTiO3, Na0.5K0.5NbO3 etc.) as promising bone substitute has been discussed. The results of several published studies from the author’s research group are summarized to highlight the cytocompatibility and histocompatibility of those perovskites. Further, the influence of incorporation of these piezoelectric materials as secondary phases in a bioactive matrix in improving the electromechanical response of composite has also been discussed briefly. It is perceived that this review will stimulate further research to explore the biomedical applications of these functional oxides. © 2019, The Indian Institute of Metals - IIM.